Suicidal behavior and associated factors among holy water users at Northwest, Ethiopia, 2023: an institution based cross-sectional study - Kassahun, Gedefaw Tegegne; Addis, Fikir; Mossie, Tilahun Belete; Belete, Habte; Munie, Birhanu Mengist (Frontiers in Psychiatry, 2024)
Background Suicide is a serious cause of mortality that affects families, communities, and the entire country. Because of a lack of national systematic reporting for cause-specific mortality, a high level of stigma, and religious non-acceptance, suicidal behavior is an under-reported and concealed cause of death in the majority of low- and middle-income countries. Objective The aim of this study was to assess the prevalence of suicidal behavior and associated factors among holy water users at the Andassa Saint George Monastery, 2023. Methods An institution-based cross-sectional study was conducted at the Andassa Saint George Monastery from 5 April to 5 May 2023. A systematic random sampling method was utilized to select 423 study participants and the Suicidal Behaviors Questionnaire—Revised was used to assess suicidal behavior. The data were gathered using the epicollect5 software with a face-to-face interview method then exported to SPSS-25 for analysis. A binary logistic regression model was used and all variables in a bivariate analysis with a p-value of less than 0.25 were entered into a multivariable logistic regression model, and statistical significance was declared at a p-value of less than 0.05. Results The prevalence of suicidal behavior among holy water users was 9.7% (95% CI: 7.1–12.4). Being female [2.632 (1.206–5.748)], living alone [2.52 (1.06–5.97)], and having depression [3.03 (1.32–6.99)], epilepsy [3.82 (1.28–11.40)], and diabetes mellitus [3.37 (1.229–9.25)] were significantly associated with suicidal behavior. Conclusion In this study, almost 1 in 10 had engaged in suicidal behavior in their lifetime. Several risk factors for suicidal behavior were identified, including being female, living alone, and having diabetes mellitus, epilepsy, and depression.